2013
DOI: 10.1007/jhep10(2013)159
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an asymptotic S matrix for perturbative quantum gravity

Abstract: The infrared behavior of perturbative quantum gravity is studied using the method developed for QED by Faddeev and Kulish. The operator describing the asymptotic dynamics is derived and used to construct an IR-finite S matrix and space of asymptotic states. All-orders cancellation of IR divergences is shown explicitly at the level of matrix elements for the example case of gravitational potential scattering. As a practical application of the formalism, the soft part of a scalar scattering amplitude is related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 46 publications
2
137
0
Order By: Relevance
“…However in [17], the factor S (1) in (1.1) relating the 5 and 4 point amplitude was found to remain uncorrected at one loop in a scheme with the soft limit taken prior to removing the IR cutoff. 3 In the recent work [20,21] (see also [22]) it was shown that a properly defined S-matrix utilizing the gravity version of the Kulish-Faddeev construction [23] is free of all IR divergences. This may be the proper context for the discussion, as it is hard to have a symmetry of an S-matrix without an S-matrix!…”
Section: Jhep08(2014)058mentioning
confidence: 99%
“…However in [17], the factor S (1) in (1.1) relating the 5 and 4 point amplitude was found to remain uncorrected at one loop in a scheme with the soft limit taken prior to removing the IR cutoff. 3 In the recent work [20,21] (see also [22]) it was shown that a properly defined S-matrix utilizing the gravity version of the Kulish-Faddeev construction [23] is free of all IR divergences. This may be the proper context for the discussion, as it is hard to have a symmetry of an S-matrix without an S-matrix!…”
Section: Jhep08(2014)058mentioning
confidence: 99%
“…is the anti-Hermitian operator appearing in the construction of Faddeev-Kulish state [4] with φ = 1. In contrast to M and M c , the IR-finite Faddeev-Kulish amplitude M FK is given by…”
Section: Relation To Faddeev-kulish Amplitudesmentioning
confidence: 99%
“…These states can be interpreted as Fock states dressed by an infinite number of soft bosons, which are commonly referred to as the boson clouds. It has been shown that using a set of such states as basis yields well-defined, infrared finite S-matrix elements [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The standard Dyson S-matrix between these asymptotic states is then free of infrared singularities. This Faddeev-Kulish method was extended to perturbative quantum gravity in [4]. It should be noted that the Faddeev-Kulish construction is valid in QED only for massive charged particles.…”
Section: Jhep01(2018)142mentioning
confidence: 99%